Investor's Preference and Awareness in Financial Instruments in Nepal - Neupane, Krishna Prasad; Adhikari, Naba Raj; Budhathoki, Dhurba Kumar (Morgan Journal of Interdisciplinary Research Studies, 2024)
This research aimed to investigate the awareness and investment preferences of Nepalese investors across various sectors. A descriptive approach was employed to examine perceptions. The study predominantly relied on primary data collected through a questionnaire, utilizing the mailed questionnaire method. A total of 60 completed questionnaires were systematically analyzed. The findings indicate that investors prioritize sufficient returns and lower risk over social status when it comes to securities investment. Key factors influencing their security choices include Earnings per Share (EPS), rate of return, Dividend per Share (DPS), and company management. Motivating factors for securities investment include dividends, capital gains, bonus shares, and liquidity, while right shares and voting rights hold lesser importance. Debt and preferred stock in the Nepalese securities market lack attractive returns, leading investors to show less inclination toward these securities due to perceived risks and issues related to liquidity and marketability. Furthermore, it was observed that a majority of investors establish an investment policy when engaging in securities investment.